PRACTICAL ASPECTS OF APIXABAN USE IN CLINICAL PRACTICE: VIEW POINT OF CLINICAL PHARMACOLOGIST - D. A. Sychev; I. I. Sinitsina; G. Yu. Zakharova; M. I. Savel'eva; A. V. Ryabova; A. V. Kryukov; A. Yu. Yurovskii (Рациональная фармакотерапия в кардиологии)
Apixaban is a "new" oral anticoagulant, direct Xa factor inhibitor with a good evidence base of the efficacy in the prevention of ischemic stroke in patients with atrial fibrillation. The article is devoted to apixaban use in clinical practice: examination before apixaban administration, clinical situation when laboratory control and monitoring are needed, drugs interactions (at the level of CYP3A4, P-gp), management of patients with bleeding because of apixaban therapy (including antidotes application), perioperative management of patients receiving apixaban.